Anteseden Niat Beli Ulang Pelanggan Café (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
One type of business that is currently growing rapidly is the business in the food and beverage sector such as cafes and this condition has resulted in increasingly fierce competition so it is very important to know customer repurchase intentions. This research was conducted with the aim to determine the effect of perceived price, product quality, and service quality on repurchase intentions. This research was conducted in a café in Payangan District, Gianyar Regency. The size of the population is not known with certainty so that the number of sample members is set at 90 people by accidental sampling technique. The Likert scale is used to get responses from respondents to the statements contained in the questionnaire as a data collection method. Multiple linear regression was chosen as a data analysis technique with SPSS software. The results of the determination analysis prove that 77.2 percent of repurchase intentions are formed by a combination of perceived price, product quality, and service quality. The results of the partial analysis prove each of the price perceptions. Product quality and service quality have a positive and significant effect on repurchase intentions.